Skeletal health in DYRK1A syndrome - Otte, Elysabeth D.; Roper, Randall J. (Frontiers in Neuroscience, 2024)
DYRK1A syndrome results from a reduction in copy number of the DYRK1A gene, which resides on human chromosome 21 (Hsa21). DYRK1A has been implicated in the development of cognitive phenotypes associated with many genetic disorders, including Down syndrome (DS) and Alzheimer’s disease (AD). Additionally, overexpression of DYRK1A in DS has been implicated in the development of abnormal skeletal phenotypes in these individuals. Analyses of mouse models with Dyrk1a dosage imbalance (overexpression and underexpression) show skeletal deficits and abnormalities. Normalization of Dyrk1a copy number in an otherwise trisomic animal rescues some skeletal health parameters, and reduction of Dyrk1a copy number in an otherwise euploid (control) animal results in altered skeletal health measurements, including reduced bone mineral density (BMD) in the femur, mandible, and skull. However, little research has been conducted thus far on the implications of DYRK1A reduction on human skeletal health, specifically in individuals with DYRK1A syndrome. This review highlights the skeletal phenotypes of individuals with DYRK1A syndrome, as well as in murine models with reduced Dyrk1a copy number, and provides potential pathways altered by a reduction of DYRK1A copy number, which may impact skeletal health and phenotypes in these individuals. Understanding how decreased expression of DYRK1A in individuals with DYRK1A syndrome impacts bone health may increase awareness of skeletal traits and assist in the development of therapies to improve quality of life for these individuals.